A neutral auxiliary ligand enhanced dysprosium(iii) single molecule magnet. Issue 22 (17th May 2018) - Chen, Xiao-Xiang; Ma, Fang; Xu, Mei-Xing; Bi, Jin-Cheng; Sun, Hao-Ling; Wang, Bing-Wu; Gao, Song
Abstract : An approximately equatorial three-coordinated dysprosium(iii ) complex DyL2 [N(SiMe3 )2 ] (L = bis(2-(2, 5-dimethyl-1 H -pyrrol-1-yl)ethyl)amine) with an additional neutral auxiliary pyrrole ligand was synthesised and structurally characterized. Abstract : An approximately equatorial three-coordinated dysprosium(iii ) complex DyL2 [N(SiMe3 )2 ] (L = bis(2-(2, 5-dimethyl-1 H -pyrrol-1-yl)ethyl)amine) with an additional neutral auxiliary pyrrole ligand was synthesised and structurally characterized. The magnetic property measurement shows that it is an equatorial charge distributed field-induced single-molecule magnet. Ab initio calculations reveal that the neutral pyrrole ligand plays an important role in stabilizing the ground doublet and thus enhancing the magnetic anisotropy.